Quadruple plasmon-induced transparency and tunable multi-frequency switch in monolayer graphene terahertz metamaterial. (19th January 2022) - Li, Yuhui; Xu, Yiping; Jiang, Jiabao; Ren, Liyong; Cheng, Shubo; Yang, Wenxing; Ma, Chengju; Zhou, Xianwen; Wang, Ziyi; Chen, Zhanyu
Abstract: A monolayer graphene metamaterial composed of a graphene block and four graphene strips, which has the metal-like properties in terahertz frequency range, is proposed to generate an outstanding quadruple plasmon-induced transparency (PIT). Additional analyses show that the forming physical mechanism of the PIT with four transparency windows can be explained by strong destructive interference between the bright mode and the dark mode, and the distributions of electric field intensity and electric field vectors under the irradiation of the incident light. Coupled mode theory and finite-difference time-domain method are employed to study the spectral response characteristics of the proposed structure, and the theoretical and simulated results are in good agreement. It is found that a tunable multi-frequency switch and excellent optical storage can be achieved in the wide PIT window. The maximum modulation depth is up to 99.7%, which corresponds to the maximum extinction ratio of 25.04 dB and the minimum insertion loss of 0.19 dB. In addition, the time delay is as high as 0.919 ps, the corresponding group refractive index is up to 2755. Thus, the proposed structure provides a new method for the design of terahertz multi-frequency switches and slow light devices.